Infrared Spectroscopic Characterization of Photoluminescent Polymer Nanocomposites - Kyle Gipson; Kathryn Stevens; Phil Brown; John Ballato (Journal of Spectroscopy)
Organicallycoated inorganic nanoparticles were synthesized to produce photoluminescent nanocomposites based on a polymethyl methacrylate (PMMA) matrix. The nanoparticles comprised organic ligands (acetylsalicylic acid, ASA, and 2-picolinic acid, PA) attached to the lanthanum trifluoride (LaF3) host crystals that were doped with optically active terbium III (Tb3+) and synthesized using solution-based methods. The ligands were employed to functionalize the surface of Tb3+:LaF3 nanocrystals to aid in dispersing the nanoparticles. In order to confirm the presence of the constituents within the inorganic-organic system, the nanoparticles were characterized by infrared spectroscopy and energy-dispersive X-ray spectroscopy. Absorption peaks observed from infrared spectroscopy for all the polymer nanocomposites loaded with organic surface treated nanocrystals exhibited peaks that were not present in undoped PMMA but were characteristic of the dopant and the ligand.